PENGARUH EARNING PER SHARE TERHADAP HARGA SAHAM. STUDI KASUS PADA PT. CHAROEN POKPHAN INDONESIA - Nurhayati, Immas (inovator, 2016)
Capital market is very dynamic industry, constantly changing and has an attractive high interdependence with other financial services sector, the domestic, regional and global levels. These characteristics have consequences for capital market participants and regulators to be able to adapt and prepare for the dynamics of change. Creativity of the capital market is the key to success in the face of changes that occur in economics and politics, both at national and international environment. Investors expect a return in investment (R). Return is the overall results obtained from the investment, both derived from dividends, interest or capital gains (the difference between selling price and the purchase of securities). To get the optimal return, before investing you should do an analysis of the issuer’s investors would have chosen. Information about the company can be known through the financial statements. One aspect that attracted the attention of investors on the company’s financial performance is information about the company’s net profit. By analyzing the net profit (earnings per share) investors can expect a net profit received from each of its shares. Additionally earning pershare is an indicator of corporate performance that is one of the important information needed to buy or sell in stock exchange. This study aims to determine how the development of net income, earnings per share PT Charoen Pokphan Indonesia, Tbk in 2005 until 2009 and to determine the extent of the influence of Earning Per Share (EPS) for the average stock price. The data used in this study is a secondary data consisting of stock prices will further processed to obtain an average price and earnings pershare. As the sample in this study would have taken the average share price of the years 2005-2009. Based on descriptive analysis, the net profit of PT Charoen Pokphand Indonesia, Tbk , in five periodsfrom 2005-2009, is constantly increasing. Increase in net income will caused the increase in EPS. Similarly, the average stock price Based on regression analysis, it can be concluded, on the increase (decrease) in EPS by 1 rupiah, will result in an increase (decrease) the average share price of 18.15 rupiahs. Based on t test, obtained a yield of 0.01 or <5% alpha indicating a rejection of H0 and accept H1. Demonstrate the significance of the results, which means there is a positive and significant relationship between the variables pershare earnings on stock prices. Correlation coefficient of 0.959 indicates a very strong close relationship between the variables EPS and average stock price. Based on the coefficient of determination (R Square) or the degree of contribution persahre earnings on stock prices, the results obtained 0.920, showing earnings per share of which contribute greatly by 92%, stock price and the remaining 8% in the influence of other variables.